The halopriming of seeds improves the germination, growth, physiological and phytochemical attributes of tomato under saline conditions - ul Sahar, Najam; Khatoon, Naseem; Majeed Mangrio, Abdul; Ali Rindc, Nadir; Rafiq, Muhammad (Emirates Journal of Food and Agriculture, 2023)
The low seed germination response and seedling growth of crops to salinity is common problem in Pakistan. To overcome this problem, seed priming is used as an economic and effective approach. Present study was conducted to evaluate the effects of halopriming of seeds on germination, growth and yield of tomato under saline conditions. The seeds of tomato variety ‘Raja’ were primed with 0, 50 mM and 100mM of NH4NO3, KNO3, and (NH4) 2SO4 solutions for 12 and 24 hours. The primed seeds were irrigated separately with tap water, saline water, and Hoagland solution with saline water. The results indicated that halopriming of tomato seeds with KNO3, NH4NO3 and (NH4) 2SO4 significantly increased the germination percentage (GP) from 58% (unprimed) to 95% (primed) while decreased the mean germination time (MGT) from 7.44 days (unprimed) to 4.6 days (primed). A significant increase was observed in the height of plant, leaf area, number of leaves, shoot and root biomass, number of fruits per plant, etc. in primed plants irrigated with Hoagland solution under saline conditions. Similarly, the halopriming with NH4NO3 and KNO3 also enhanced the chlorophyll pigments, lycopene contents, total soluble sugars, total proteins, total phenolic contents and total flavonoids in primed plants irrigated with Hoagland solutions under salt stress. Furthermore, proline contents were increased in primed plants irrigated with NaCl solution as compared to other treatments and control. In conclusion, KNO3 and NH4NO3 are more effective priming agents than (NH4) 2SO4 were positively affected the germination, plant height, physiological and biochemical attributes in tomato plants under saline and non-saline conditions. The supplement of Hoagland solution under salt stress further improves the morphological, physiological and biochemical attributes of tomato.